2009
DOI: 10.1210/en.2008-0899
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Peroxisome Proliferator-Activated Receptor-γ in Key Neuronal Subsets Regulating Glucose Metabolism and Energy Homeostasis

Abstract: In addition to increasing insulin sensitivity and adipogenesis, peroxisome proliferator-activated receptor (PPAR)-gamma agonists cause weight gain and hyperphagia. Given the central role of the brain in the control of energy homeostasis, we sought to determine whether PPARgamma is expressed in key brain areas involved in metabolic regulation. Using immunohistochemistry, PPARgamma distribution and its colocalization with neuron-specific protein markers were investigated in rat and mouse brain sections spanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 26 publications
12
116
0
4
Order By: Relevance
“…Similarly, the glial cell markers S100 and GFAP are expressed in a great variety of normal and pathological tissues [50,51]. On the other hand, neural cells can express mesodermal-specific markers such as the osteogenic markers osteopontin and osteocalcin and the adipogenic marker PPAR [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the glial cell markers S100 and GFAP are expressed in a great variety of normal and pathological tissues [50,51]. On the other hand, neural cells can express mesodermal-specific markers such as the osteogenic markers osteopontin and osteocalcin and the adipogenic marker PPAR [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PPAR isoforms has been detected in mouse, ovine and human pituitary gland [13,14] and in rodent hypothalamus [15], but their significance in the regulation of reproductive functions at the level of hypothalamic-pituitary (HP) remains poorly understood. It has been demonstrated that PPARg activation by TZDs inhibited the development of pituitary adenomas in mice and humans [18,19] but did not affect the secretion of prolactin (PRL), follicle-stimulating hormone (FSH) or luteinizing hormone (LH) by ovine pituitary or LH by murine LbetaT2 gonadotrophic pituitary tumor cell line [16].…”
Section: Ppars and The Hypothalamic--pituitary (Hp) Axismentioning
confidence: 99%
“…The second PPAR discovered in mammals, as homologous to PPAR-alpha, was PPARgamma [64,65] PPAR-gamma exhibits an expression pattern broadly similar to PPARalpha, including, notably, low but detectable expression in the brain [64], including in neurons [66]. Like PPAR-alpha, PPAR-gamma is activated by a variety of lipophilic substances Compared with the neuroprotective effects of PPAR-alpha agonists described above, neuroprotective effects of PPAR-gamma agonists have been far more robustly reported, and have been the subject of several recent reviews [68,69].…”
Section: Neuroprotective Effects Of Ppargamma Agonistsmentioning
confidence: 99%